Treadle pump irrigation in Malawi: adoption, gender and benefits - Kamwamba-Mtethiwa, J.; Namara, Regassa E.; Fraiture, Charlotte de; Mangisoni, J.; Owusu, E. (Wiley, 2012)
As part of their irrigation strategy, the government and non-governmental organizations (NGOs) in Malawi are actively promoting the use of treadle pumps in smallholder irrigation. The positive impact of treadle pumps on food security and poverty reduction in Malawi and elsewhere in sub-Saharan Africa is well documented. However, few studies have analysed the adoption dynamics and dissemination approaches of treadle pumps. This study uses a logit model to analyse the factors influencing treadle pump adoption among a stratified random sample of 100 adopters and 100 non-adopters in two districts in Malawi. The results indicate that relatively well-off farmers have a significantly higher probability of adopting the treadle pumps than poor farmers. This raises questions about dissemination approaches and targeting, because treadle pumps are typically geared towards poor smallholders. The study further indicates differences between male and female adopters. Female adopters are more likely to pay for subsidized treadle pumps in cash. Male adopters mostly acquire their pumps through a loan. Women tend to spend the additional income on food for the household while men tend to spend it mostly on non-food items. It is therefore likely that treadle pump adoption by women will positively impact on household food security, though it also adds to women's workload.